AB0620 Long-Term Outcome of SLE Patients with Joint Ultrasound Abnormalities Associated to Hand Inflammatory Arthralgia. (9th June 2015) - Salman Monte, T.C.; Corzo, P.; Torrente-Segarra, V.; Polino, L.; Lisbona, M.; Orpinell, L.; Marqués, D.; Carbonell Abellό, J.
Abstract : Background: In the past years, the information about the utility of joint ultrasound (US) in SLE is raising. We know SLE patients with hand and wrist arthralgia might show joint US abnormalities (1). It is yet to be demonstrated the utility of joint US in the prediction of worse clinical outcome in SLE patients. Objectives: To describe and to compare long-term clinical outcome in SLE patients who showed inflammatory joint US abnormalities associated to the presence of hand and wrist arthralgia. Methods: A prospective longitudinal study of patients with SLE (fullfilling ACR 1982 criteria) who showed baseline hand and wrist arthralgia and inflammatory joint US abnormalities that were compared to healthy SLE patients were assessed. These patients were regularly attended at the Rheumatology department at Hospital del Mar. Two study groups were defined: "cases, " patients with hand and wrist arthralgia and morning stiffness>1h and abnormal joint US at baseline; and "controls" patients without arthralgia or morning stiffness and normal US at baseline. An abnormal joint US was defined by the presence of joint effusion and/or synovial hypertrophy and/or tenosynovitis with or without Power Doppler signal in wrist and/or 2nd-5th MCP joints and/or 2nd-5th PIP joint as defined OMERACT-7 (2). Clinical, serological and treatmets parameters were registered at baseline, during the follow up time and in the last assessment. Results: Conclusions: Patients with hand and wrist arthralgia and abnormal joint US showed a higher prevalence of joint involvement during follow-up, as well as a greater need for treatment with synthetic DMARDs such as hydroxychloroquine and methotrexate, compared with those without such symptoms who also had normal joint US. The joint US might help us on the study ofSLE patients with hand and wrist arthralgia who also show inflammatory abnormalities by joint US. Patients with abnormal joint US at baseline seems to suffer a worse joint involvement outcome. References: Torrente-Segarra V et al. Joint Bone Spine. 2013;80:402-6. Cheung PP et al. Int J Rheum Dis.2014;17:776-81. Acknowledgements: Sergi Mojal. AMIB. Disclosure of Interest: None declared